A Qualitative Study of Experiences of Participants in Cardiac Rehabilitation. Issue 4 (July 2018) - Yates, Bernice C.; Vazquez Hernandez, Mari L.; Rowland, Sheri A.; Bainter, Denise E.; Schulz, Paula; Hanson, Corrine K.
Abstract : Purpose: Maintenance of lifestyle changes after cardiac rehabilitation (CR) is suboptimal. In addition, partners of cardiac patients are invited to participate in CR educational sessions and implicitly expected to assist patients with their lifestyle changes. The purpose of this study was to qualitatively examine patient and partner perceptions of phase 2 CR 3 mo after completion of the program. Methods: A purposive sample of 11 couples (patients post–heart surgery and their spouses) was interviewed following completion of CR. Semistructured, in-person interviews were conducted with patients and spouses separately. Data were analyzed using line-by-line coding to identify themes. Results: Themes were identified in relation to program elements of CR. Exercise themes were as follows: (1) benefitted from exercise and (2) felt held back. Education themes were as follows: (1) received basic education and (2) needed more personalized information. CR environment themes were as follows: (1) developed confidence; (2) made social comparisons; and (3) helped to have partner there. Conclusion: Overall, participant perceptions of exercise, education, and the CR environment were very positive. Nevertheless, there is a need to improve educational efforts within CR to rely less on "canned" presentations and more on participants developing their own self-management methods to maintain a healthy lifestyle after CR. Abstract : This study examined perceptions of patients and partners in a phase 2 cardiac rehabilitation (CR) within 3 mo of completing the program. Participant perceptions of CR were, overall, very positive. Participants reported that they benefitted from the exercise sessions; however, they wanted more personalized information from the educational sessions.